1 Laws of New Hampshire: Province Period 537 (Albert Stillman Batchellor ed., 1904) - (:unkn) unknown (My University, 1692)
Changed the militia from all "persons" over sixteen to all males over 16. For arms, everyone had to be "well provided w'th a well fixed gun or fuse," plus "Sword or hatchet." Along with the typical colonial requirements for gunpowder and bullets, a knapsack, a cartridge box, a powder horn, and flints. Further, "every Soldier Shall have at his habitation & abode one pound of good pouder & twenty Sizable bullets."
Keywords: MILITIAS; REQUIRED POSSESSION